The Impact of Housing Wealth on Stock Liquidity - Luo, Juan; Xu, Limin; Zurbruegg, Ralf (Review of Finance, 2017)
We document a housing wealth effect on the stock liquidity of local firms. We first demonstrate that the heterogeneity of homeownership rates across geographical areas can explain variations in the impact that changes in house prices have on local stock liquidity. We then show, consistent with expectations that an increase in housing wealth leads to a reduction in household risk aversion, that the liquidity of lottery stocks and stocks dominated by individual investors rises. We also show that it promotes local liquidity commonality and reduces the proportion of firm-specific information revealed in stock returns.